Pengaruh Work-Life Balance Dan Pengembangan Karier Terhadap Retensi Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada PT Inti Sukses Sumatera - Andini Pustika Sari; Marta Widian Sari; Yosi Puspita Sari (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the effect of work-life balance and career development on employee retention with job satisfaction as an intervening variable at PT Inti Sukses Sumatera. This research uses a quantitative method with a survey approach. Data were collected through questionnaires distributed to employees as research respondents. Data analysis was conducted using statistical analysis to examine direct and indirect effects among variables. The results show that work-life balance and career development have a positive and significant effect on job satisfaction. In addition, work-life balance and career development also have a positive and significant effect on employee retention. Job satisfaction is proven to mediate the effect of work-life balance and career development on employee retention. Therefore, improving work-life balance and career development supported by job satisfaction can increase employee retention at PT Inti Sukses Sumatera